Decreasing of Wet Deck Slamming - Victor A. Dubrovsky (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
Shocks by waves, slamming, of the wet deck (the bottom of inter- hull structure) is a specific disadvantage of all multi-hull ships. It means the decreasing of such slamming is an important problem of a multi-hull ship designing and creation. The problem is divided by two parts: motion mitigation and shock elimination. Some methods of longitudinal motion mitigation of various multi- hulls are examined and compared. In addition, some methods of shock pressure decreasing are shown too. As the results, some general and particular recommendations are proposed.